The Memory of the “Revival Process” in the Newest Bulgarian Novel (2011–2017) - Yanev, Kristiyan (Poznańskie Studia Slawistyczne, 2019)
The aim of this article is to explore the most recent literary representations of the so-called “Revival process” in Bulgarian history or the renaming of the Bulgarian Muslim and Turkish minorities in the 1980s in Zlatko Enev’s Requiem for Nobody (Реквием за никого, 2011), Martin Marinov’s The Veil (Булото, 2014), Miroslav Penkov’s The Stork Mountain (Щъркелите и планината, 2016), and Liudmila Mindova’s Novel for the Name (Роман за името, 2017). The analysis focuses on the outlining of the thematic and structural similarities between the novels and the different approaches toward the depiction of trauma. I argue that this new trend is an attempt to rethink the legacy of the communist past and conceptualize collective trauma.